Consumer Trust in AI-Generated Advertisements. A Comparative Study of AI and Human-Created Advertising Content - Musawer Hakimi; Nazar Mohammad Parsa; Mohammad Nawab Turan (Universitas Pendidikan Nasional, 2026)
The rise of generative artificial intelligence in advertising has created pressing questions about whether consumers can or will trust content they know a machine has crafted. This study examined how 412 adult consumers evaluated AI-generated versus human-created advertisements across six product sectors, investigating the mechanisms of perceived authenticity, cognitive engagement, and emotional response as mediators, and AI literacy as a boundary condition. Using a mixed experimental-survey design followed by structural equation modelling, mediation analysis, and cluster analysis, results showed that AI-generated advertisements received significantly lower trust ratings (d = 0.89), yet this gap narrowed substantially among participants with higher AI literacy. Perceived authenticity emerged as the strongest mediator, accounting for 31.2% of the indirect effect. Importantly, trust in AI advertising increased with repeated exposure, suggesting that familiarity attenuates initial scepticism. These findings yield actionable implications for practitioners and advance theoretical understanding of technology-mediated persuasion.